2013
DOI: 10.1155/2013/318548
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Lacaziosis in Bottlenose Dolphins (Tursiops truncatus) in Japan

Abstract: Lacaziosis, formerly called lobomycosis, caused by Lacazia loboi, is a zoonotic mycosis found in humans and dolphins and is endemic in the countries on the Atlantic Ocean. Although the Japanese coast is not considered an endemic area, photographic records of lacaziosis-like skin lesions were found in bottlenose dolphins (Tursiops truncatus) that were migrating in the Goto Islands (Nagasaki Prefecture, Japan). We diagnosed 2 cases of lacaziosis in bottlenose dolphins captured simultaneously at the same coast wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 26 publications
3
37
0
2
Order By: Relevance
“…However, their DNA sequences are not available. More recently, 3 groups in Japan ( 14 , 15 ) and Spain ( 16 ), who also used molecular methods, reported similar observations for several dolphin species including, T. truncatus and Lagenorhynchus obliquidens , which had skin granulomas and yeast-like cells in infected tissues. These studies showed that glycoprotein 43 ( gp43 )–like and ITS partial DNA sequences isolated from infected dolphins placed the etiologic agent of skin granulomas among human P. brasiliensis strains.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…However, their DNA sequences are not available. More recently, 3 groups in Japan ( 14 , 15 ) and Spain ( 16 ), who also used molecular methods, reported similar observations for several dolphin species including, T. truncatus and Lagenorhynchus obliquidens , which had skin granulomas and yeast-like cells in infected tissues. These studies showed that glycoprotein 43 ( gp43 )–like and ITS partial DNA sequences isolated from infected dolphins placed the etiologic agent of skin granulomas among human P. brasiliensis strains.…”
mentioning
confidence: 64%
“…We analyzed DNA sequences of pathogens isolated from 6 dolphins with lacaziosis/lobomycosis captured in the Indian River Lagoon. Diverse geographic locations of dolphins in the Atlantic Ocean ( 13 , 16 ) and the Pacific Ocean ( 14 , 15 ) and specimens evaluated by molecular methods provide additional support for placement of the etiologic agent of keloidal-like granulomas in dolphins within P. brasiliensis (Figure 3). Because these geographic locations, especially for cases from Japan ( 14 , 15 ), have different ecologic niches than locations for P. brasiliensis in South America ( 4 ), detection of dolphins infected with an uncultivated P. brasiliensis type in these ecosystems is a major finding.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Characterized by greyish, whitish to slightly pink, verrucous lesions, often in pronounced relief, that may ulcerate and form plaques, lobomycosis 2 and LLD naturally affect common bottlenose dolphins Tursiops truncatus and Guiana dolphins Sotalia guianensis from Brazil, Ecuador, Peru, Colombia, Venezuela and Suriname (de Vries and Laarman, 1973;Simões-Lopes et al, 1993;Van Bressem et al, 2007;Bermudez et al, 2009;Daura-Jorge and Simões-Lopes, 2011). Lobomycosis is caused by a dimorphic fungus resembling Lacazia loboi (Taborda et al, 1999;Hauboldt et al, 2000) but genetically more closely related to Paracoccidioides brasiliensis (order Onygenales, family Ajellomycetaceae) (Rotstein et al, 2009;Esperon et al, 2011;Ueda et al, 2013). LLD is 1 Moreno, I.B., Ott, P.H., Tavares, M., Oliveira, L.R., Borba, M.R., Driemeier, D., Nakashima, S.B., Heinzelmann, L.S., Siciliano, S. and Van Bressem, M-F. (2008) Mycotic dermatitis in common bottlenose dolphins (Tursiops truncatus) from southern Brazil, with a confirmed record of lobomycosis disease.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopically, lemon-shaped, budding yeast-like organisms resembling Lacazia loboi (Taborda et al 1999) were detected in skin lesions sampled in T. truncatus (Caldwell et al 1975, Simões-Lopes et al 1993, Paniz-Mondolfi et al 2012, Van Bressem et al 2007) and a S. guianensis from the Americas (Symmers 1983), and in a S. plumbea from South Africa (Lane et al 2014; Table 1). However, recent molecular characterization of the 43 kDa glycoprotein coding gene and of ribosomal DNA from lesions sampled in T. truncatus from the USA and Cuba, and in Indo-Pacific bottlenose dolphins T. aduncus from Japan, indicated that the yeast-like organism infecting these dolphins is more closely related (94−97%) to Paracoccidioides brasiliensis than to L. loboi (Rotstein et al 2009, Esperón et al 2012, Ueda et al 2013. Paracoccidioides spp.…”
Section: Introductionmentioning
confidence: 99%